Policy or circumstances? A Synthetic Control Method for evaluating Brazil's economic boom under Lula - Jaeho Jung; Kisung Dennis Kwon (Economies, 2025)
This study empirically examines whether Brazil's remarkable economic growth from 2003 to 2010 was primarily driven by Lula's policies or favorable global economic conditions using the Synthetic Control Method - a robust causal inference technique for assessing policy effects when randomized controlled trials are infeasible and only one treated unit exists. Our analysis suggests that Brazil's economic performance was largely attributable to external circumstances, while the policies of Lula's administration may not have significantly enhanced growth. This study demonstrates the robustness of the results through leave-one-out distribution, the ratio of postintervention-period root mean square prediction error (RMSPE) to preintervention-period RMSPE, and in-space placebo tests.
Keywords: 330; counterfactual analysis; policy evaluation; Latin America; growth determinant